2003
DOI: 10.1097/00005131-200310000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Chondrocyte Apoptosis Following Impact Load

Abstract: The current data strongly indicate that in vivo chondrocyte apoptosis can be stimulated by the application of a single, rapid impact load and that the extent of chondrocyte apoptosis is related to the amount of load applied. The contribution chondrocyte apoptosis makes to the development of posttraumatic arthritis following joint injury or intra-articular fracture still remains to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 23 publications
1
62
0
3
Order By: Relevance
“…The lower threshold we observed might be related to the use of immature porcine cartilage explants. High mechanical stress can induce cell death (14,31), and the degree of chondrocyte death is related to the intensity of mechanical stress (32). Hashimoto et al showed that chondrocyte death occurred early during the process of cartilage degeneration in OA (9).…”
Section: Discussionmentioning
confidence: 99%
“…The lower threshold we observed might be related to the use of immature porcine cartilage explants. High mechanical stress can induce cell death (14,31), and the degree of chondrocyte death is related to the intensity of mechanical stress (32). Hashimoto et al showed that chondrocyte death occurred early during the process of cartilage degeneration in OA (9).…”
Section: Discussionmentioning
confidence: 99%
“…Standard light microscopy is one of the most insensitive methods to detect apoptosis. However, in detecting lymphocyte apoptosis it is highly specific if certain morphologic changes are identified, and it has been used extensively in previous studies (37)(38)(39)(40). The morphologic changes specific to lymphocyte apoptosis consist of cell shrinkage with condensed nuclei (pyknosis) and nuclear fragmentation (karyorrhexis).…”
Section: Detection and Quantification Of Apoptosismentioning
confidence: 99%
“…It has been shown that mechanical injury to cartilage explants results in chondrocyte apoptosis with a loss of glycosaminoglycans [58] and changes in gene expression [59]. Similarly, Borelli Jr. et al [60] have shown that in vivo chondrocyte apoptosis can be caused by a single impact load. Furthermore in vitro chondrocyte necrosis can be induced by non-physiological stimuli [61].…”
Section: Discussionmentioning
confidence: 99%